Annotated Catalog of the Fossil Invertebrates Described by, and Named for, William More Gabb (1839–1878) - Groves, Lindsey T.; Squires, Richard L. (Zootaxa, 2018)
William More Gabb [1839–1878] described 1163 fossil invertebrate taxa: Protozoa [1 species], Porifera [1 genus, 2 species], Cnidaria [12 species], Bryozoa (with G.H. Horn) [1 family, 8 genera, 67 species], Brachiopoda [15 species], Annelida [7 species], Mollusca [Bivalvia: 15 genera, 2 subgenera, 412 species; Gastropoda: 1 family, 2 subfamilies, 42 genera, 8 subgenera, 489 species; Scaphopoda: 10 species; Cephalopoda: 1 family, 3 genera, 51 species], Arthropoda [Crustacea: 2 species; Cirripedia 1 species], and Echinodermata [11 species]. Listed herein are all fossil taxa named by Gabb, type localities, institutional depository, and remarks concerning current taxonomic status, when known. An annotated list of Gabb’s fossil references is also included. Also listed herein are 134 fossil invertebrate taxa and 33 living mollusk taxa named for him.